ECAC use case of optimised pre-tactical time of arrival adjustments to reduce probability of separation infringements - Gatsinzi, Dany; Saez Nieto, Francisco Javier; Madani, Irfan (Elsevier, 2018)
Currently, a maximum allowable number of aircraft (A/C) entering and or within a sector for a given period is fixed. Anytime this threshold is reached, involved A/C are regulated by Air Traffic Flow and Capacity Management (ATFCM) to maintain an acceptable Air Traffic Controllers’ (ATCOs’) workload. This threshold is determined regardless of particular expected air traffic complexity, which may result from potential conflicts inherently in A/C’s flight plans that may greatly affect the ATCOs’ workload. This paper proposes a new ATFCM Demand and Capacity Balancing (DCB) methodology, applied to mitigate potential conflicts between A/C’s trajectories at pre-flight level, in order to reduce the current ATCO’s workload attributed to Separation Management (SM) interventions. This purpose is achieved through minor adjustments on A/C’s Times of Arrival (TOAs) at conflicted en-route junctions. The adjustments of A/C’s TOAs are implemented through minor changes on A/C’s speed profile, applied before and after each conflicted junction, while maintaining each A/C’s departure and Targeted Time of Arrival(TTA) at destination. The paper postulates that these TOA adjustments could be easily transformed into pre-tactical ATFCM DCB measures, assuming that ATFCM will issue Reference Business Trajectories (RBTs) containing time constraints at junctions, introduced to reduce the probability of conflicts. A case study of European Civil Aviation Conference (ECAC) air traffic network using real flight plan data is presented to show the validity of the methodology.
Keywords: ATFCM; TBO; ECAC; CD&R; DCB; junction; TOA